Intracranial Electroencephalography in Pediatric Severe Traumatic Brain Injury. Issue 3 (March 2020) - Appavu, Brian; Foldes, Stephen; Temkit, M'hamed; Jacobson, Austin; Burrows, Brian T.; Brown, Danni; Boerwinkle, Varina; Marku, Iris; Adelson, P. David
Abstract : Objectives: Electroencephalography is used in neurocritical care for detection of seizures and assessment of cortical function. Due to limited resolution from scalp electroencephalography, important abnormalities may not be readily detectable. We aimed to identify whether intracranial electroencephalography allows for improved methods of monitoring cortical function in children with severe traumatic brain injury. Design: This is a retrospective cohort study from a prospectively collected clinical database. We investigated the occurrence rate of epileptiform abnormalities detected on intracranial electroencephalography when compared with scalp electroencephalography. We also investigated the strength of association of quantitative electroencephalographic parameters and cerebral perfusion pressure between both intracranial and scalp electroencephalography. Setting: This is a single-institution study performed in the Phoenix Children's Hospital PICU. Patients: Eleven children with severe traumatic brain injury requiring invasive neuromonitoring underwent implantation of a six-contact intracranial electrode as well as continuous surface electroencephalography. Interventions: None. Measurements and Main Results: Visual detection of epileptiform abnormalities was performed by pediatric epileptologists. Association of intracranial and scalp electroencephalography total power, alpha percentage, and alpha-delta power ratio to cerebral perfusion pressure was performed using univariate dynamic structural equations modeling. Demographic data were assessed by retrospective analysis. Intracranial and scalp electroencephalography was performed in 11 children. Three of 11 children had observed epileptiform abnormalities on intracranial electroencephalography. Two patients had epileptiform abnormalities identified exclusively on intracranial electroencephalography, and one patient had seizures initiating on intracranial electroencephalography before arising on scalp electroencephalography. Identification of epileptiform abnormalities was associated with subsequent identification of stroke or malignant cerebral edema. We observed statistically significant positive associations between intracranial alpha-delta power ratio to cerebral perfusion pressure in nine of 11 patients with increased strength of association on intracranial compared with scalp recordings. Conclusions: These findings suggest that intracranial electroencephalography may be useful for detection of secondary insult development in children with traumatic brain injury. Abstract : Supplemental Digital Content is available in the text.